Azyumardi Azra's Thoughts on the Contribution of Multicultural Islamic Education to Strengthening Indonesian Nationalism - Nur Laili Indah Soraya; Intan Saffana Zahira; Nailul Amaliyah; Pramudita Bagas Jati; Muh. Ikhwan Nurosid; Fidella Ainindias Tabita; Arkan Khalid Ibrahim (International Tatho Academics, 2026)
This qualitative study, conducted as a literature review, aims to describe Azyumardi Azra’s views on strategies for strengthening Indonesian nationalism through multicultural Islamic education. The findings indicate that, in Azyumardi Azra’s view, multicultural education not only fosters tolerance but also serves as the ideological foundation for inclusive nationalism. In Indonesia’s pluralistic society, this education shifts the paradigm of nationalism from homogeneous to pluralistic, transforming differences into a source of national strength. This study contributes to the assertion that multicultural education strengthens social cohesion, builds an adaptive national identity, and prevents identity-based horizontal conflicts.